STUDY THE EFFECT OF SERUM CHEMERIN IN TYPE II DIABETES MELLITUS PATIENTS WITH AND WITHOUT DIABETIC RETINOPATHY - KALYANI CHAKKARAI,; SANTHINI GOPALAKRISHNAN,; THIVYAH PRABHA,; DIVYA PALAKSHA, (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objective: Diabetic retinopathy (DR) arises from oxidative stress, inflammation, and pro-angiogenic signaling. Chemerin, a pleiotropic adipokine, links adipogenesis, glucose homeostasis, and inflammatory pathways. This study aimed to quantify serum chemerin in type 2 diabetes mellitus (T2DM) with and without DR. Methods: This was comparative cross-sectional study. Adults were grouped as healthy controls (n=110), T2DM without DR (n=110), and T2DM with DR (n=110). Serum chemerin was measured by enzyme-linked immunoassay. Group differences were assessed using one-way analysis of variance (ANOVA) with Tukey’s HSD post hoc when assumptions were met or Games-Howell when variances were unequal. Within-DR staging (non-proliferative DR [NPDR] vs. proliferative DR [PDR]) used independent-samples tests. Results: Chemerin differed significantly across groups (one-way ANOVA, p<0.01) and was higher in T2DM with DR than in T2DM without DR and controls. Mean±standard deviation chemerin concentrations were as follows: Controls 150.04±21.06 ng/mL; T2DM without DR 246.77±123.82 ng/ mL; T2DM with DR 259.33±133.32 ng/mL. Pairwise Tukey’s HSD comparisons were significant (all p<0.05). Within the DR cohort, serum chemerin was higher in PDR than NPDR (independent-samples t-test, p<0.05). Conclusion: Elevated chemerin in DR supports adipokine-driven inflammation and angiogenesis in DR progression. Chemerin may aid risk stratification alongside glycemic and lipid indices, reinforcing the importance of early T2DM control and DR screening.